2020
DOI: 10.1097/aog.0000000000004026
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perspectives on Audio-Only Virtual Prenatal Visits Amidst the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Pandemic

Abstract: OBJECTIVE: To evaluate patient satisfaction after integration of audio-only virtual visits into a pre-existing prenatal care schedule within a large, county-based system during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. METHODS: We implemented audio-only prenatal virtual visits in response to the SARS-CoV-2 pandemic within a large, county-based prenatal care system serving predominantly women with low socioeconomic status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
109
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(126 citation statements)
references
References 13 publications
5
109
2
5
Order By: Relevance
“… Gilbert et al. (2020) Satisfaction scores were high for phone and virtual consultations (90 and 85%, respectively) Clinicians rated virtual consultation as 78/100 for clinicians Holcomb et al. (2020) 99% participants rated their visit “good” or “very good Holtz et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Gilbert et al. (2020) Satisfaction scores were high for phone and virtual consultations (90 and 85%, respectively) Clinicians rated virtual consultation as 78/100 for clinicians Holcomb et al. (2020) 99% participants rated their visit “good” or “very good Holtz et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2020) France Quantitative, Prospective Survey ENT April 6–10, 2020 100 of the 125 patients in the ENT tele-consultation over the 7-day inclusion period completed the survey Mean age= 51; 2:3 M/F ratio Lyon, France Questionnaire LOE VI Gilbert et al. (2020) UK qi orthopedic march 16-april 20, 2020 215 patients; 103 clinicians RNOC Survey LOE VI Holcomb et al. (2020) USA Descriptive cross-sectional Prenatal visit March 17-May 31, 2020 283 out of 421 pregnant women who participated in at least one visit agreed to participate (65% response rate); 89% females; 84% Whites; 66.8% with college degrees Texas Telephone survey LOE VI Holtz (2020) USA Descriptive cross-sectional Not identified March 31-April 20, 2020 1011 participated the survey but data from 434 participants who had used telemedicine were included in their analysis; 89% females Survey LOE VI Itamura et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some health facilities in the United States have successfully implemented antenatal remote care during COVID-19 to ensure safe and effective obstetric care. For example, obstetric facilities in Florida, Texas and New York reduced their in-person visits from 11 to 6, 13 to 9, and 11 to 6 respectively [9][10][11]. They developed their ANC schedules based on expert recommendations, established WHO and national guidelines, and the OB Nest model developed at Mayo Clinic for women experiencing low-risk pregnancies [12].…”
mentioning
confidence: 99%
“…High satisfaction levels were observed across all telemedicine encounters irrespective of mode (synchronous or asynchronous) and disease type; for instance, all participants (114) were satisfied in vascular consultations, 20 median satisfaction 9 (IQR 8-10) was reported in rheumatology, 21 and 99% of respondents reported that their needs were met for prenatal consultations through audio virtual visit only. 22 In case of teledentistry, provided through virtual clinic and telephonic consultations, 97% of patients were satisfied with the virtual clinic and 94% were satisfied with telephonic consultations. 23 A cross-sectional observational study reported high patient satisfaction in case of skin disorders through synchronous model (live interaction between a patient and a dermatologist) and the store forward model (through e-mails).…”
Section: Professionals New York-presbyterian/weill Cornell Medicalmentioning
confidence: 94%